Front Cover: A New Bispyrroloiminoquinone Alkaloid From a Thai Collection of Clavelina sp. (Asian J. Org. Chem. 7/2021). Issue 7 (5th July 2021) - Grkovic, Tanja; Ruchirawat, Somsak; Kittakoop, Prasat; Grothaus, Paul G.; Evans, Jason R.; Britt, John R.; Newman, David J.; Mahidol, Chulabhorn; O'Keefe, Barry R.
Abstract : The National Cancer Institute's (NCI) Natural Products Repository is one of the largest and most diverse publicly available collections of natural product extracts used for drug discovery research. In this work, a new bispyrroloiminoquinone alkaloid was isolated from a Thai collection of the ascidian Clavelina sp. The structure of the new natural product 16‐hydroxy‐17‐oxindole wakayin was deduced from interpretation of 1D and 2D NMR as well as mass spectrometry data. In addition, we compared its NCI‐60 cytotoxic activity to other structurally related pyrroloiminoquinone‐containing marine natural products in our library. More information can be found in the Communication by Barry R. O'Keefe et al (graphic designed by Jasmine A. Loyal) .